Exploring the impact of media and information on self-reported intentions to vaccinate against COVID-19: A qualitative interview-based study. Issue 5 (30th November 2022) - Parsons Leigh, Jeanna; Halperin, Donna; Mizen, Sara J.; FitzGerald, Emily A.; Moss, Stephana Julia; Fiest, Kirsten M.; Di Castri, Antonia; Stelfox, Henry T.; Halperin, Scott
ABSTRACT: Background: The World Health Organization declared vaccine hesitancy a top threat to global health following resurgence of vaccine-preventable diseases close to eradication in many countries (e.g. measles). Vaccines are effective in preventing severe illness, hospitalization, and death from COVID-19, yet there remains a small proportion of the eligible population who choose not to vaccinate. Social media and online news sources are opportunities for targeted public health interventions to improve vaccine uptake. This study reports the results of a semi-structured interview study that explored the influence of media and information on individuals' self-reported intentions to vaccinate against COVID-19. Methods: A qualitative descriptive study was employed to gain insight from a diverse group of individuals. Adult participants were recruited through a related COVID-19 study; we used a maximum variation sampling technique and purposively sampled participants based on demographics. Interviews were conducted from February 2021 to May 2021. Themes from interviews were summarized with representative quotations according to the 3C Theoretical Framework (Confidence, Complacency, Convenience). Results: Key themes identified following thematic analysis from 60 participants included: vaccine safety, choice of vaccine, fear mongering, trust in authority, belief in vaccinations (Confidence); delaying vaccination (Complacency); confusing information, access to vaccines and information (Convenience). While most participants intended to vaccinate, many expressed concerns and hesitancy. Conclusions: COVID-19 vaccine hesitancy prevents universal immunization and contradictory messages in media are a source of concern and fear. The success of future vaccine campaigns will depend upon authorities' ability to disseminate accessible, detailed, and consistent information promoting public confidence.